Tinjauan Hukum Islam Menurut Ulama Kota Sampit terhadap Depo Sampah di Sekitar Lingkungan Pendidikan (Studi Kasus Depo Sampah SAHATI 04, Kecamatan Baamang, Kabupaten Kotawaringin Timur, Kalimantan Tengah) - Muhammad Fazrianur Arridho; Rizki Nurramadhina; Anwar Hafidzi; Muhammad Noor Ridani (Fakultas Syariah UIN Antasari, 2022)
This paper has a background in the case of the existenceof the DEPO 04 SAHATI landfill which was built around theeducational facilities of SMP Negeri 3 Sampit, thus disrupting theteaching and learning activities carried out by teachers andstudents due to the odor generated from the temporary shelter. Themethod used is descriptive qualitative field research by conductinginterviews with the clerics of Sampit City. The results obtainedfrom this research are related to the legal determination of theexistence of Temporary Shelters around the SMPN 3 Sampit schooland the need for more intensive management from managers andpublic awareness of the importance of managing waste to minimizethe risks that can interfere with teaching and learning activities.